2020
DOI: 10.1021/acs.jpcc.0c06657
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of the Co Cations on the Destabilization of the Ferrimagnetic Alignment in Co-Ferrite Nanoparticles with Tunable Structural Defects

Abstract: The key role of the structural defects on the magnetic properties of cobalt ferrite nanoparticles (NPs) is investigated by complementary local probes: element-and site-specific X-ray magnetic circular dichroism (XMCD) combined with high-resolution transmission electron microscopy of individual NPs. A series of monodisperse samples of 8 nm NPs with a tunable amount of structural defects were prepared by thermal decomposition of Fe(III) and Co(II) acetylacetonates in the presence of a variable concentration of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…This series of samples was also an excellent model to study by element-and site-specific XMCD the cation moments and site distribution since samples showed similar size distribution and stoichiometry. 71,93 The Fe L2,3 edge XAS and XMCD spectra showed the typical features previously described for CoXFe3-xO4. 148,149 In particular, XMCD spectra of Fe showed the three characteristic peaks corresponding to Fe L2,3 edges: the lowest negative energy peak corresponded to octahedral Fe 2+ (Oh), the positive peak to tetrahedral Fe 3+ (Td), and the highest negative peak to Fe 3+ (Oh).…”
Section: From the Inside To The Outside: How The Nanostructure And Th...supporting
confidence: 64%
See 1 more Smart Citation
“…This series of samples was also an excellent model to study by element-and site-specific XMCD the cation moments and site distribution since samples showed similar size distribution and stoichiometry. 71,93 The Fe L2,3 edge XAS and XMCD spectra showed the typical features previously described for CoXFe3-xO4. 148,149 In particular, XMCD spectra of Fe showed the three characteristic peaks corresponding to Fe L2,3 edges: the lowest negative energy peak corresponded to octahedral Fe 2+ (Oh), the positive peak to tetrahedral Fe 3+ (Td), and the highest negative peak to Fe 3+ (Oh).…”
Section: From the Inside To The Outside: How The Nanostructure And Th...supporting
confidence: 64%
“…So far, an overview of the parameters that affect the synthesis of Fe3-xO4 NP and the importance of achieving strict control over them has been discussed. In this section, we are going to focus on the special case of cobalt ferrite CoxFe3-xO4 NP where, although some of the previous strategies can also be applied, 62,71,93,94 an additional level of complexity is added associated with the requirement of two different metal precursors.…”
Section: The Case Of Cobalt Ferritementioning
confidence: 99%
“…Therefore, the distribution of Co 2+ (O h ) is expected have dominant effects on the MCA. Such modifications of magnetic anisotropy induced by the distribution of Co 2+ (O h ) are also reported for the CoFe 2 O 4 nanoparticles [21][22][23]. The cation distribution in these films has been studied using XMCD by Wakabayashi et al From the comparison of y and the normalized MCA (the magnitude of MCA divided by M ) as functions of the film thickness d plotted in Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Recently, Moya et al have shown that different values of the inversion parameter lead to different values of the total spin magnetic moment, due to a lowering of the magnetic coupling and to a canting of the cation magnetic moments, in particular for Co 2+ cations. Two reasons were given by these authors to explain this effect: the first one is a direct consequence of the noninverse structure, with Co 2+ (Td)-O-Fe 3+ (Oh) antiferromagnetic superexchange interactions lower than the dominant Fe 3+ (Td)-O-Fe 3+ (Oh) ones; the second reason potentially comes from structural relaxations induced by other defects [95]. From our calculations (see Supplemental Material [43]), we indeed found that the antiferromagnetic coupling constant between cations in Oh and in Td atomic sites is reduced by 2-3 meV, for both CFO and NFO, when the inversion degree λ decreases from 1 to 0.875.…”
Section: Influence Of the Inversion Degree On The Physical Propertiesmentioning
confidence: 99%